Strategi Pembinaan Karakter Disiplin Siswa oleh Guru PPKn Kelas VII dalam Pembelajaran di MTs Negeri Samarinda - Ika Pramudita; Aloysius Hardoko; Jamil Jamil; Asnar Asnar; Wingkolatin Wingkolatin; Endang Herliah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the strategies used by PPKn teachers of grade VII at MTs Negeri Samarinda in fostering students' disciplined character during learning. This study uses a qualitative research type with research subjects consisting of 1 PPKn teacher of grade VII and 6 students of grade VII through the stages of observation, interviews, and documentation. The results of the study indicate that the development of disciplined character carried out by PPKn teachers went well where the teachers implemented various strategies, namely: Development of discipline in dressing is carried out through role models, conditioning at the beginning of learning, and giving sanctions. Development of time discipline is carried out through role models, giving tiered sanctions, and arranging activities and duration of activities in the classroom according to estimates. Development of task discipline is carried out by giving assignment deadlines, clear assignment guidelines, and feedback on student assignment results. Meanwhile, development of behavioral discipline is carried out through role models, setting behavioral rules during learning, and giving tiered sanctions. During the implementation of the above strategies, it was seen that students had shown their discipline well.